Kepemimpinan Wanita di Perpustakaan IAIN Raden Fatah Palembang - Nurmalina Nurmalina (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract: Library as a source of information (resource center) is a very strategic place in the dissemination of information. Reciprocation of an organization is influenced by the applied management, especially top managers factor. Selection of top managers should be based on good managerial skills within the organization, so the important thing is the ability (capability) not on anything, so everyone has the right to occupy that position. With the expected capabilities of the organization will be able to run properly in accordance with the vision, mission, and programs that have been implemented. This is in accordance with a saying that we have to determine the position of a person according to his ability.